Cost-effectiveness of sacral nerve stimulation and percutaneous tibial nerve stimulation for faecal incontinence - Hounsome, Natalia (Therap Adv Gastroenterol, 2018)
BACKGROUND: Subcutaneous sacral nerve stimulation is recommended by the United Kingdom (UK) National Institute for Health and Care Excellence (NICE) as a second-line treatment for patients with faecal incontinence who failed conservative therapy. Sacral nerve stimulation is an invasive procedure associated with complications and reoperations. This study aimed to investigate whether delivering less invasive and less costly percutaneous tibial nerve stimulation prior to sacral nerve stimulation is cost-effective. METHODS: A decision analytic model was developed to estimate the cost-effectiveness of percutaneous tibial nerve stimulation with subsequent subcutaneous sacral nerve stimulation versus subcutaneous sacral nerve stimulation alone. The model was populated with effectiveness data from systematic reviews and cost data from randomized studies comparing both procedures in a UK National Health Service (NHS) setting. RESULTS: Offering percutaneous tibial nerve stimulation prior to sacral nerve stimulation (compared with delivering sacral nerve stimulation straight away) was both more effective and less costly in all modeled scenarios. The estimated savings from offering percutaneous tibial nerve stimulation first were £662–£5,697 per patient. The probability of this strategy being cost-effective was around 80% at £20,000–£30,000 per quality-adjusted life-year (QALY). CONCLUSION: Our analyses suggest that offering patients percutaneous tibial nerve stimulation prior to sacral nerve stimulation can be both cost-effective and cost-saving in the treatment of faecal incontinence.